EXPERT SYSTEM FOR HEPATITIS DISEASE DIAGNOSIS USING FUZZY TSUKAMOTO METHOD BASED ON WEBSITE IN RSUD PRINGSEWU - Elvia Fajarwati; Niva Kurnia Sari (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
The liver is a vital organ in humans, which functions as the formation and secretion of bile, and as a detoxification of poisons. Hepatitis is difficult to detect at an early stage but handling hepatitis at an early stage will greatly help the recovery of patients. With the increase in the number of Hepatitis sufferers besides being caused by an unhealthy lifestyle, it is also caused by the delay in handling when experiencing initial symptoms. So, this study aims to design an Expert System to diagnose hepatitis with a website-based Fuzzy Tsukamoto method so that it can facilitate access to information for people who need information about hepatitis. Website-based system design using the Fuzzy Tsukamoto method because it is considered flexible enough and has a tolerance to data that is not appropriate and based on natural language. Expert system as a tool in determining whether the patient is suffering from hepatitis or not with the Tsukamoto fuzzy method. The results of the discussion can be concluded that this system is designed with a simple model so that it can be used by the community.